Observation of multiple beta-induced Alfvén eigenmodes driven by runaway electrons in EAST Ohmic discharge - C.X. Luo; L. Zeng; J. Bao; X. Zhu; T. Tang; R.R. Ma; S.Y. Lin; T.H. Shi; J.P. Qian; H.Q. Liu; Z.Y. Qiu; Y.F. Liang; et al. (Nuclear Fusion)
Multiple Beta-induced Alfvén eigenmodes (BAEs) excited by runaway electrons (REs) have been observed in low-density Ohmic discharges in the EAST tokamak. The toroidal mode number is mainly n = −1 and they rotate in the electron diamagnetic drift direction. These modes in the low frequency range from 10 to 25 kHz, are found to be unstable when the electron density decreases to less than 0.65 × 10 ^19 m ^−3 . BAEs depend sensitively on the RE current fraction. By decreasing electron density, the resistive current is replaced by that carried by the REs. Then more branches of unstable BAEs, which located at different rational surfaces, are simultaneously observed, indicating that BAEs depend sensitively on the plasma beta contributed from REs. Simulation results provided by the global eigenvalue code magnetohydrodynamic Alfvén spectra suggest trapped energetic particles are responsible for the destabilization of these BAEs, which match the resonance condition and the mode locations are close to the plasma boundary.